The Role of Communication Channels on Implementation of Housing Construction Projects in Nairobi County, Kenya - Achar , Milkah; Chebii , Pamela; Mugo , James (African Journal of Education,Science and Technology (AJEST), 2021)
The implementation of housing projects should aim to get construction work completed within stipulated time and within the costs estimated. The frequencies of stalled construction projects, the government dismantling some illegally constructed buildings, collapsing buildings and the disturbing death toll that accompanies these events, have become significant issues in Kenya. The purpose of the study is to examine the roles that communication channels have on implementation of housing construction in Nairobi City County Government, Kenya. The study used both descriptive and inferential statistics for the analysis technique. Target population was 256 participants (professionals engaged in design, approval and construction of public housing projects within Nairobi.) It was evident that the model: Overall Project Implementation= 6.311 +0.00319 (Channels of Communication) is a significant predictor of overall project implementation. After conducting data analysis, the results of the hypothesis were found to be significant: Channels of communication are key to the execution of construction projects. The results of the regression analysis show that improving the means of communication channels by a unit increases the overall project completion by 0. 00319. The study concluded that in the implementation of construction projects, channels of communication is of significant impact.